(untitled) (American Journal of Aquaculture and Animal Science, 2025)
This study assesses the use of Dracaena arborea extract as a diluent during artificial propagation of Clarias gariepinus. Apparently healthy male and female African catfish (Clarias gariepinus) broodstock with average weight of 2.5kg were used for this study. The male fish was dissected and the milt collected into a dry vial. The milt was assessed at different dilution ratios, specifically 0.1 ml of milt to 1 ml (D1), 2 ml (D2), 3 ml (D3), and 4 ml (D4) of Dracaena arborea extract, while the control was 0.1 ml of undiluted milt. The experiment was laid out in a complete randomized design (CRD) involving 4 treatments and a control, each replicated 3 times. Results showed no significant (P>0.05) difference in the milt percentage motility and milt count. The highest milt percentage motility occurred in D2 (57.11%) while the lowest (40.67%) was observed in the control group. There was significant difference (P<0.05) in the milt motility duration between the treatments and the control which ranged from 3.22±0.05mins to 2.05±0.03mins. Significant decreased was observed in the milt motility duration with increasing concentration of Dracaena arborea extract. The result of reproductive performance shows significant (P<0.05) difference in the percentage hatchability of eggs withthe highest in D1 (93.78%) and the lowest in D4 (47.01%). No significant (P>0.05) difference was recorded in water temperature, pH and dissolved oxygen, however, Dracaena arborea extract significantly (P>0.05) impacted water conductivity which increased as the concentration of the extract increased. The result of the study indicates that Dracaena arborea extract could serve as milt diluent during artificial propagation of Clarias gariepinus which can be exploited to improve reproductive performance in fish seeds production.